The Study of Kinetics and Isotherms Using Lignocellulose as an Adsorbent for Biobutanol Separation - บุญสมบัติ, อัครินทร์; เหลืองนฤมิตชัย, อาภาณี (Progress in Applied Science and Technology, 2017)
As a result of fossil fuels that tend to lessen continually, the production in alternative energy such as butanol is investigated. Biobutanol is produced via ABE fermentation which forms mixture of Acetone, Butanol, and Ethanol then the separation process is considered. In this work, adsorption process using biomass from corncob and pineapple peel was applied in batch experiment. Both samples were pretreated by 2 methods to modify the composition of cellulose, hemicellulose, and lignin which may affect the adsorption process. The results show that, among 2 biomass and 2 methods, Pineapple peel which treated by isolation of lignin method (PP2) can selectively adsorb butanol over acetone and ethanol. In addition, it has the highest adsorption capacity of butanol. In terms of kinetics, it revealed that the adsorption of butanol in binary system using PP2 consistent with the Pseudo-second order model then the equation was constructed to predict the adsorption behavior. Moreover, the Langmuir and Freundlich isotherms were applied at various butanol concentrations. It was found that the Langmuir model was fitted and the equilibrium isotherm equation was acquired. Compared to other works, the PP2 has calculated adsorption capacity of 65.44 mg/g nearly the ZSM-5 zeolite, indicating that the porosity may not essential than the hydrophobicity.